Herbicide usage for invasive non‐native plant management in wildland areas of North America. Issue 1 (29th June 2016) - Wagner, Viktoria; Antunes, Pedro M.; Irvine, Michael; Nelson, Cara R.
Summary: In North America, herbicides are commonly used to control non‐native invasive plants on public wildlands. Little is known about the magnitude, efficacy and financial costs of this practice, although this information is crucial for policymakers, researchers, land managers, pesticide producers and the general public. In Canada and Mexico, herbicide usage data have not been tracked by agencies. In the USA, data archiving has been implemented by federal land managing agencies. However, while area sprayed and amounts of herbicides have been documented to varying degrees, efficacy and financial costs have not been recorded in a standardized and consistent manner and data publication has been insufficient. Based on requested data, we estimate that in the USA, half a million hectares of public wildlands were sprayed with herbicides in 2010, representing 201 tonnes. Although non‐selective, glyphosate was the most commonly used active ingredient. Synthesis and applications . Increasing efforts by land management agencies to collect and share herbicide usage data is a key step towards narrowing the knowledge gap on herbicide usage in invasive non‐native plant management on public wildlands. Land managers and policymakers in particular would benefit from an enhanced flow of information on efficacy, costs and effects of herbicides.